Possibilities of complex food-processing of quince - Furulyás Diána; Nagy Orsolya; Papp Nóra; Stefanovits-Bányai Éva; Stéger-Máté Mónika; International Symposium on Analytical and Environmental Problems (21.) (2015) (Szeged) (2015)
The food industry generate large amount of such by-products, which may also contain unused, valuable components. In this research the possibilities of complex food industry usability were investigated for three species of quince (Cydonia oblonga Mill.) (“Angersi, Bereczki, Konstantinápolyi”). The nutritional characteristics of quince skin, pulp and ovary were compered. We measured the nutritional properties: dry matter content, pectin and acid content, polyphenol and flavonoid content. Moreover the rheological properties were investigated. The results were analyzed with statistics method. The results of dry content are not significant, but between samples of quince parts the pectin and acid content have significant difference. It was largest amount of polyphenol in the pulp of quince, and the most of flavonoid content were measured in the skin of quince. Concluding from the rheological properties ‘Angersi’ species are suggested to use as jam, quince jelly or natural texturing, while ‘Konstantinápolyi’ species are recommended to use for the production of fiber juices or syrups. Because of theirs high pectin content, the skin and ovary suitable to use as production of pectin or natural texturing. Due to high antioxidant capacity of skin and ovary may use at manufacture of natural antimicrobial agents, dietary supplements or functional food.